An analytic algorithm to calculate the inclination, ascending node, and semimajor axis of spectroscopic binary orbits using a single speckle measurement and the parallax - Docobo, Jose Angel; Campo, P P; Andrade, Manuel; Horch, Elliott P (Astrophysical Bulletin, 2014)
It is well known that in spectroscopic binary orbits, the inclination, the ascending node, and the semimajor axis remain undetermined, therefore the principal objective of this research is to establish an analytic methodology for the calculation of these parameters for spectroscopic binaries, both single-lined (SB1) and double-lined (SB2). In other words, the goal is to determine their “three-dimensional” orbits using a single speckle measurement (ρ, θ, t) and the parallax (π). Moreover, estimates of the individual masses of each system can also be obtained. The proposed algorithm was successfully applied to SB1 systems: YSC 148 (HD 37393) and CHR 225 (HD 34318), and SB2 systems: LSC 1 Aa1,2 (HD 200077) and Mkt 11 Aa, Ab (HD 358). In this late case, previously determined spectroscopic and visual orbits have been used to compare and contrast the results obtained from them with our results. The methodology presented is especially interesting for those cases in which it is only possible to resolve the spectroscopic binary in the zones of maximum angular separation by optical means thereby making it impossible to avail of sufficient observations in order to calculate the visual orbit. © Pleiades Publishing, Ltd. 2014.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/094-814-675-311-054 tex.type: [object Object]
Keywords: dept.phy; general; high angular resolution—techniques; interferometric—binaries; techniques

The three-dimensional orbit and physical properties of the binary COU 2031 (WDS 04464+4221, HIP 22196, HD 30090) - Docobo, Jose Angel; Griffin, R F; Tamazian, V S; Horch, Elliott P; Campo, P P (Monthly Notices of the Royal Astronomical Society, 2014)
We report a comprehensive study of the binary system COU 2031, based on simultaneous and independent astrometric visual and speckle observations and on radial-velocity measurements. The similarity of the two orbital solutions allows us to obtain not only a consistent 3D orbit and a precise value of the parallax of the system but also to determine the physical properties of the components. © 2014 The Authors.
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/132-132-335-733-638 tex.type: [object Object]
Keywords: Binaries: spectroscopic; Binaries: visual; Stars: individual: COU 2031; dept.phy; peer-reviewed

Limits on stellar companions to exoplanet host stars with eccentric planets - Kane, Stephen R; Howell, Steve B; Horch, Elliott P; Feng, Ying; Hinkel, Natalie R; Ciardi, David R; Everett, Mark E; Howard, Andrew W; Wright, Jason T (The Astrophysical Journal, 2014)
Though there are now many hundreds of confirmed exoplanets known, the binarity of exoplanet host stars is not well understood. This is particularly true of host stars that harbor a giant planet in a highly eccentric orbit since these are more likely to have had a dramatic dynamical history that transferred angular momentum to the planet. Here we present observations of four exoplanet host stars that utilize the excellent resolving power of the Differential Speckle Survey Instrument on the Gemini North telescope. Two of the stars are giants and two are dwarfs. Each star is host to a giant planet with an orbital eccentricity >0.5 and whose radial velocity (RV) data contain a trend in the residuals to the Keplerian orbit fit. These observations rule out stellar companions 4-8 mag fainter than the host star at passbands of 692 nm and 880 nm. The resolution and field of view of the instrument result in exclusion radii of 0.″05-1.″4, which excludes stellar companions within several AU of the host star in most cases. We further provide new RVs for the HD 4203 system that confirm that the linear trend previously observed in the residuals is due to an additional planet. These results place dynamical constraints on the source of the planet's eccentricities, place constraints on additional planetary companions, and inform the known distribution of multiplicity amongst exoplanet host stars. © 2014. The American Astronomical Society. All rights reserved..
24 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/031-289-457-778-141 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: individual (HD 4203; HD 168443; HD 1690; HD 137759); techniques: Radial velocities; techniques: high angular resolution